SUSTAINABILITY OF FISHERY POND POLYCULTURE WITH AND WITHOUT MANGROVE INTEGRATION - Eva Dolorosa; . Masyhuri; . Lestari; . Jamhari (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
This research aims to analyze the sustainability of two types of fishery pond polyculture of milkfish-tiger shrimp with and without mangrove integration on small-scale farms. Sustainability dimensions considered in this research included are the ecology, economy, social-culture, technology-infrastructure, and laws-institutions as the dimensions analyzed.  The performance of each aspect was analyzed by using Multi-dimensional scaling (Rapfish) and leverage analysis. The result shows that the current multidimensional sustainability status  of  the fishery  pond   polyculture  both  with  and  without  mangrove  integration was less sustainable  (sustainability index of 44.98 and 36.18 respectively). The result of leverage analysis indicates that out of 73 attributes, there were 16 and 23 sensitive attributes respectively that affect the sustainability of polyculture fishpond with and without mangrove integration. These attributes should be managed immediately in order to improve the sustainability index of fishery pond polyculture, this includes organic pesticides application, source of capital, the availability of seeds of milkfish and tiger shrimp, market location, selling price, waste treatment technology, availability of agribusiness facilities and infrastructure, aquaculture technology, information technology, standardizing the quality of fishery products, availability of micro finance institution and others.